Representações de germanidade, escola e professor no Allgemeine Lehrerzeitung für Rio Grande do Sul [Jornal Geral para o professor no Rio Grande do Sul] - Arendt, Isabel Cristina (Universidade do Vale do Rio do Sinos, 2005)
This thesis studies the views and discussions about Germanism (Deutschtum), school and teacher conveyed in the journal Allgemeine Lehrerzeitung für Rio Grande do Sul, Vereinsblatt des Deutschen Evangelischen Lehrervereins in Rio Grande do Sul [General Teacher’s Journal for Rio Grande do Sul, a publication of the Association of German Evangelical Teachers in Rio Grande do Sul], edited and published by the Deutscher Evangelischer Lehrerverein von Rio Grande do Sul [Association of German Evangelical Teachers from Rio Grande do Sul] between the years 1902 and 1938. We approached this topic with a frame of reference based on cultural history. The journal’s editors and contributors, most of whom were German teachers allocated to urban schools, address topics such as Deutschtum, school and teacher, deal with issues like identity, set models of conduct and recommend reading material for teachers working in “German-Brazilian” evangelical schools, the jounal’s primary readership. We also present the views exposed on
Keywords: escola; escola evangélico-luterana; imprensa; representações; Rio Grande do Sul; germanidade; professor; printing press; school; teacher; views about; deutschtum; evangelical schools; Ciências Humanas